2020
DOI: 10.4067/s0718-58392020000100003
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of media formulation for axillary shoot multiplication of the red-peeled sweet potato (Ipomoea batatas [L.] Lam.) ‘Abees’

Abstract: Sweet potato (Ipomoea batatas [L.] Lam.) is an important food crop that is cultivated and consumed worldwide, and its nutritional value makes it especially important in developing countries. However, sweet potato plants produced using conventional vegetative propagation can be prone to several diseases, thereby hindering crop yield. Therefore, micropropagation techniques are useful for producing higher quality plant material. The aim of the present study was to determine the optimal medium formulation for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…In the present study, BA was the most effective for shoot proliferation from nodal segments of A. africana among all the cytokinins tested. Similar observations were made for other plants including Ipomoea batatas (Dewir et al, 2020), Crataeva nurvala , and Psiadia arguta (de Souza et al, 2007). The ability of BA to initiate cell division and development of lateral buds makes it superior to other cytokinins, as it plays a key role in breaking bud dormancy (Revathi et al, 2019;Dewir et al, 2020;Rajput et al, 2020).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the present study, BA was the most effective for shoot proliferation from nodal segments of A. africana among all the cytokinins tested. Similar observations were made for other plants including Ipomoea batatas (Dewir et al, 2020), Crataeva nurvala , and Psiadia arguta (de Souza et al, 2007). The ability of BA to initiate cell division and development of lateral buds makes it superior to other cytokinins, as it plays a key role in breaking bud dormancy (Revathi et al, 2019;Dewir et al, 2020;Rajput et al, 2020).…”
Section: Discussionsupporting
confidence: 67%
“…Similar observations were made for other plants including Ipomoea batatas (Dewir et al, 2020), Crataeva nurvala , and Psiadia arguta (de Souza et al, 2007). The ability of BA to initiate cell division and development of lateral buds makes it superior to other cytokinins, as it plays a key role in breaking bud dormancy (Revathi et al, 2019;Dewir et al, 2020;Rajput et al, 2020). de Souza et al (2007 also observed that lower concentrations of BA (0.25 and 0.5 mg/l) were superior in shoot multiplication of P. arguta, just as we observed in A. africana.…”
Section: Discussionsupporting
confidence: 66%
“…The supremacy of BA among the cytokinins was also reported in Agave salmiana (Puente-Garza et al, 2015 ), Prunus africana (Komakech et al, 2020 ), and A. africana (Okello et al, 2021 ). The potential of BA to commence the division of the cell, break of bud dormancy, and development of lateral buds makes it superior to other cytokinins (Dewir et al, 2020 ; Rajput et al, 2020 ). A previous report on C. equisetifolia also showed the dominance of BA over other cytokinins (Seth et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report on the synergistic effect of combination of BAP and mT on shoot multiplication of gerbera. Several researchers have described the synergistic effect of two cytokinin (Dewir et al, 2020;Lavanya et al, 2016) or auxin and cytokinin (Khanam et al, 2020;Shekhawat et al, 2021) or combinations of two cytokinin with auxin (Shekhawat et al, 2020) is also reported. A combination of auxin with cytokinin have a positive impact on shoot multiplication in many plant species (Khanam et al, 2020;Shekhawat et al, 2021).…”
Section: Shoot Multiplicationmentioning
confidence: 99%